2020
DOI: 10.1111/1440-1630.12715
|View full text |Cite
|
Sign up to set email alerts
|

Controlled choice, not choice and control: Families' reflections after one year using the National Disability Insurance Scheme

Abstract: Introduction: At least 40 percent of children with cerebral palsy and their families rely on access to allied health services, assistive technology, and require funding and expertise to achieve skills and participate in daily life. Implementation of the National Disability Insurance Scheme (NDIS) has resulted in a shift to public funding and emphasis on choice and control of services, support and assistive technology to promote social and economic participation. Families of children with cerebral palsy are inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…A new finding of this study is the identification of the differences in experiences and outcomes of home adaptations between parents who received fully funded government grants and whose workforce were appointed by their local council and those who funded them (fully or partially) and appointed contractors themselves. Although Smethurst et al ( 2021 : 205) study conducted in Australia found that ‘equipment impacts on all areas of life’, this study is the first to demonstrate the impact of home adaptations on all five aspects of at‐homeness (appropriation, at‐easeness, regeneration, rootedness and warmth) (Seamon, 1979a , 1979b ).…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…A new finding of this study is the identification of the differences in experiences and outcomes of home adaptations between parents who received fully funded government grants and whose workforce were appointed by their local council and those who funded them (fully or partially) and appointed contractors themselves. Although Smethurst et al ( 2021 : 205) study conducted in Australia found that ‘equipment impacts on all areas of life’, this study is the first to demonstrate the impact of home adaptations on all five aspects of at‐homeness (appropriation, at‐easeness, regeneration, rootedness and warmth) (Seamon, 1979a , 1979b ).…”
Section: Discussionmentioning
confidence: 62%
“…They felt powerless when those involved in the adaptation processes perhaps saw their child ‘as a burden or a cost’ (Gallo et al, 2021 : 1) or as ‘undeserving’ (Cross, 2008 ). Like families in other studies, parents said that they had to fight for (Boss et al, 2020 ; Currie & Szabo, 2019 ; Parsons & Darlington, 2021 ), prove they are deserving of and wait for the resources (Dybwik et al, 2011 ) and adaptations (Boniface & Morgan, 2017 ; Smethurst et al, 2021 ) they needed to care for their child at home. Without the correct technology and adaptations, the family were limited in their family and social activities; these findings are echoed in Smethurst et al's ( 2021 ) study.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations